2016
DOI: 10.1007/s10265-016-0896-y
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the plant non-coding RNA world

Abstract: in mouse revealed "a new continent in the RNA world", through the novel observation showing that ~73% of genomic regions are used for transcription of non-coding RNAs (Carninci et al. 2005;Katayama et al. 2005). The emergence of next-generation sequencing technologies encouraged this trend to identify a variety of non-coding RNAs. These big successes by non-coding RNA research have generated new RNA biology; now we know that RNA molecules are not only working as the intermediates between DNAs and proteins, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The molecular mechanism of heterosis is still unclear through extensive studies on genome, transcriptome and epigenetics ( Larièpe et al, 2012 ; Shen et al, 2014 ; Shao et al, 2019 ; Wang and Wang, 2022 ; Zhang, 2022 ). In recent years, several ncRNAs and their corresponding regulatory networks have been proved to play important roles in plant growth and development ( Ohtani, 2017 ; Yuan et al, 2018 ; Luan et al, 2019 ; Wang et al, 2020 ; Zhai et al, 2020 ; Chand Jha et al, 2021 ; Qiao et al, 2021 ). However, there are few studies on the role of ncRNA in plant heterosis so far, which have been conducted in maize and cabbage ( Crisp et al, 2020 ; Hou et al, 2020 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism of heterosis is still unclear through extensive studies on genome, transcriptome and epigenetics ( Larièpe et al, 2012 ; Shen et al, 2014 ; Shao et al, 2019 ; Wang and Wang, 2022 ; Zhang, 2022 ). In recent years, several ncRNAs and their corresponding regulatory networks have been proved to play important roles in plant growth and development ( Ohtani, 2017 ; Yuan et al, 2018 ; Luan et al, 2019 ; Wang et al, 2020 ; Zhai et al, 2020 ; Chand Jha et al, 2021 ; Qiao et al, 2021 ). However, there are few studies on the role of ncRNA in plant heterosis so far, which have been conducted in maize and cabbage ( Crisp et al, 2020 ; Hou et al, 2020 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid rise of modern genomics techniques, noncoding RNA or nonprotein-coding RNAs (ncRNA or npcRNA), once called genomic “dark matter,” has been discovered ( Morris and Mattick, 2014 ; Yu et al, 2019 ). By targeting to corresponding DNA, RNA and proteins, ncRNAs participate in a variety of biological processes and molecular mechanisms in plants ( Ohtani, 2017 ; Chand Jha et al, 2021 ). In rice, many experimental reports have indicated the importance of ncRNAs in growth, development, environmental response ( Yuan et al, 2018 ; Luan et al, 2019 ; Wang et al, 2020 ; Zhai et al, 2020 ; Qiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental reports have shown that ncRNAs and their target genes play important roles in plant development, environmental responses, and biotic and abiotic stress responses (Ohtani, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs are mainly classified into long noncoding RNAs (lncRNAs), which are longer than 200 nt, and small noncoding RNAs (sRNAs), which are smaller than 200 nt ( Gelaw and Sanan-Mishra, 2021 ). Many experimental reports have shown that ncRNAs and their target genes play important roles in plant development, environmental responses, and biotic and abiotic stress responses ( Ohtani, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only approximately 2% of the transcribed genome possesses protein-coding ability, and most of the transcripts are non-coding RNAs (ncRNAs) [ 1 , 2 ]. The ncRNAs are involved in a series of biological processes and pathways in organisms by acting on corresponding targets, such as DNA, RNA, and proteins [ 3 , 4 ]. Long non-coding RNAs (lncRNAs) are freshly discovered functional ncRNAs that are longer than 200 nt in length, possessing little or no coding possibility, exerting extensive regulatory effects through a variety of mechanisms [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%